DAMPAK EKONOMI PEMBATASAN SOSIAL BERSKALA BESAR TERHADAP MASYARAKAT KOTA PEKANBARU DI PROVINSI RIAU - HERISPON, HERISPON (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
This study was an analysis of the condition of the covid pandemic 19 events that occurred from the end of November 2019 to the beginning of June 2020. Pandemic events that occur in many countries in the world generally, in Indonesia and the city of Pekanbaru, Riau in particular that is the enactment Large-scale Social Restrictions (RSSL) has given an influence on the life and economic order of the community. By uses the method of literature study and analysis of real events that occur in society, it was found that the current RSSL and pandemic had weakened the joints of the economy; individuals, householdslarge companies or small companies without exception due to individual space restrictions, groups in carryes out economic activities and ended in termination of employment (FLE), temporary leave of work, finally reduced the income and consumption of the people